Headache associated with neurological deficits and cerebrospinal fluid lymphocytosis syndrome with delayed neurological deficits mimicking chronic lymphocytic meningitis: A diagnostic challenge from a tuberculosis-endemic region: Headache associated with neurological deficits and cerebrospinal fluid lymphocytosis syndrome with delayed neurological deficits mimicking chronic lymphocytic meningitis: - Modi, Sailesh; Lakkapragada, Rohit; Ponnana, Rajakumar; kanaparti, Manoj (Indian Journal of Case Reports, 2026)
Headache associated with Neurological Deficits and Cerebrospinal Fluid Lymphocytosis (HaNDL) syndrome irare, self-limiting disorder that often mimics infectious, inflammatory, and vascular diseases. We report a 42-yearold man with recurrent severe unilateral headaches accompanied by nausea, photophobia, and phonophobia.Initial investigations were unremarkable, and he was treated as status migrainosus with only transient benefit fromcorticosteroids. Cerebrospinal fluid (CSF) analysis later showed lymphocytic pleocytosis and elevated protein,raising suspicion for tuberculous meningitis despite negative microbiological studies. Antitubercular therapy wasinitiated elsewhere without clinical improvement. Repeat neuroimaging and autoimmune evaluation were normal.During hospitalization, he developed transient episodes of confusion, dysphasia, and left-sided sensory symptomswithout radiological abnormalities. A diagnosis of HaNDL syndrome was established based on recurrent migrainelike headaches, transient neurological deficits, CSF lymphocytic pleocytosis, and exclusion of alternative causes. Thepatient improved with corticosteroid therapy and remained symptom-free at 1-year follow-up.